De paisagens e infâncias em Ondjaki ou uma poética dos anos 80 - Nascimento, Marlúcia Nogueira do (2018)
This thesis deals with the relation between the configuration of spaces and childhood as an idyllic and lasting time in the narratives Bom dia camaradas (2001), Os da minha rua (2007) and AvóDezanove e o segredo do soviético (2008), by Ondjaki. The research aims at examining the representation of the spaces habitually frequented by the protagonist - home, school and street - and its relation with the sense of childhood built from the recollection of the environment of the 80s, having as reference the conception of childhood thought by Bachelard (1961) and the notion of chronotope conceived by Bakhtin (1975). It also aims at observing how Ondjaki approaches social and political dissensions in Angola from the narrator's point of view, which associates humor, lightness and lyricism. The bibliographic research prioritizes the comparative and interpretative analysis of the works of the corpus among them, placing them within the scope of the prose production of Angolan literature that contemplates children's characters in the antecedent period and the concomitant to the wars, notably A cidade e a infância (1960), by Luandino Vieira, and Quem me dera ser onda (1982) by Manuel Rui. First, an exposition of the theoretical apparatus about the categories of childhood (ARIÈS, 1960; KOHAN, 2003; POSTMAN, 1999) and space (TUAN, 1977; BACHELARD, 1957; COLLOT, 2012, 2013), as well as the presence of children's issues associated with the context of wars in Angolan literature, introducing issues that guide interpretive and comparative reading. Afterwards, the works of the corpus are analyzed, whose reading shows that: the plots are based on the affective bond maintained by the narrator with the places and the landscapes, extending to the people with whom he shares the coexistence; the social and political issues are approached from a neutral and ambiguous point of view, resulting from the simulation from the point of view of the child, associating with it the metaphorical construction of a new reality, through symbologies like rain, in Bom dia camaradas, and the explosion in AvóDezanove; there are many spaces and faces of childhood in Angolan fiction, among them, the child-soldier, the pioneer, the man in the future, marked by the mission of building the future of the country; places and landscapes embrace one's own sense of childhood as idyllic and permanent time inseparable from living space, thus becoming a chronotope.